2017
DOI: 10.1111/zsc.12249
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of North American map and sawback turtles (Testudines: Emydidae: Graptemys)

Abstract: Map turtles of the genus Graptemys are native to North America, where a high degree of drainage endemism is believed to have shaped current diversity. With 14 species and one additional subspecies, Graptemys represents the most diverse genus in the family Emydidae. While some Graptemys species are characterized by pronounced morphological differences, previous phylogenetic analyses have failed yet to confirm significant levels of genetic divergence for many taxa. As a consequence, it has been debated whether G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…For instance, [ 65 ] showed that the eight traditionally recognized species of Pseudemys reduced to only three species-level lineages in their molecular analyses. Similarly, [ 72 ] showed that the 14 currently recognized species of Graptemys, long noted for their low levels of molecular divergence [ 95 ], appeared to represent eight or nine species-level lineages at most. These findings were confirmed [ 73 ] by authors who nevertheless continued to recognize 14 species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, [ 65 ] showed that the eight traditionally recognized species of Pseudemys reduced to only three species-level lineages in their molecular analyses. Similarly, [ 72 ] showed that the 14 currently recognized species of Graptemys, long noted for their low levels of molecular divergence [ 95 ], appeared to represent eight or nine species-level lineages at most. These findings were confirmed [ 73 ] by authors who nevertheless continued to recognize 14 species.…”
Section: Discussionmentioning
confidence: 99%
“…1–5). In a recent study on the intrageneric phylogenetic relationships of Graptemys based on molecular data, Praschag et al (2017 , fig. 2) found Graptemys geographica as sister to two main clades, including one with mainly “broad-headed” species and one with “narrow-headed” species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most previous studies that have looked at the intrageneric relationships of Graptemys have found G. geographica as sister to other Graptemys species ( McKown, 1972 ; Lamb et al, 1994 ; Lamb & Osentoski, 1997 ; Stephens & Wiens, 2003 ; Wiens, Kuczynski & Stephens, 2010 ). Praschag et al (2017) determined Graptemys was taxonomically oversplit and suggested revision of its species was needed, particularly members of their “narrow-headed” species group. The present study uses a member of their broad-headed group ( Graptemys barbouri ) and a member of their narrow-headed group ( Graptemys pseudogeographica ), along with G. geographica .…”
Section: Discussionmentioning
confidence: 99%
“…One locus, the intron 1 of the RNA fingerprint protein 35 gene (R35) has been previously shown to be species-diagnostic for P. galeata and P. subrufa ( Vargas-Ramírez et al, 2010 ). The other locus, including coding and non-coding parts of the ornithine decarboxylase gene (ODC), is relatively variable in chelonians ( Fritz et al, 2012 ; Praschag et al, 2017 ) and therefore looked promising to be also species-specific. Laboratory procedures for the nuclear loci followed Praschag et al (2017) except that we applied newly designed internal primers for sequencing the R35 gene (forward: GCAAGGAAAAATGTTTG, reverse: ACGCTGACTCCATGCACA).…”
Section: Methodsmentioning
confidence: 99%